2019
DOI: 10.1103/physrevb.99.134421
|View full text |Cite
|
Sign up to set email alerts
|

Dzyaloshinskii-Moriya interaction and spin-orbit torque at the Ir/Co interface

Abstract: We studied the spin torque efficiency and the Dzyaloshinskii-Moriya interaction (DMI) of heterostructures that contain interface(s) of Ir and Co. The current-induced shifts of the anomalous Hall loops were used to determine the spin torque efficiency and DMI of [Pt/Co/X] multilayers (X=Ir, Cu) as well as Ir/Co and Pt/Ir/Co reference films. We find the effective spin Hall angle and the spin diffusion length of Ir to be ~0.01 and less than ~1 nm, respectively. The short spin diffusion length and the high conduct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 44 publications
4
19
0
Order By: Relevance
“…The value of spin diffusion length obtained for platinum is in agreement with the values found in the literature: the experimental values reported using the SP-FMR setup range from 0.5 nm [32] to 10 nm [23], with numerous values in between [10,48]. The obtained value l Ir s f = 1.3 nm is twice larger than the one presented in earlier studies [17,18] with similar FMR-based methods, and close to the one reported by spin-orbit torque technique, ∼ 1 nm [7]. That difference might be due to different Ir resistivity.…”
Section: Spin Diffusion Length and Spin Hall Angle Determinationsupporting
confidence: 91%
See 3 more Smart Citations
“…The value of spin diffusion length obtained for platinum is in agreement with the values found in the literature: the experimental values reported using the SP-FMR setup range from 0.5 nm [32] to 10 nm [23], with numerous values in between [10,48]. The obtained value l Ir s f = 1.3 nm is twice larger than the one presented in earlier studies [17,18] with similar FMR-based methods, and close to the one reported by spin-orbit torque technique, ∼ 1 nm [7]. That difference might be due to different Ir resistivity.…”
Section: Spin Diffusion Length and Spin Hall Angle Determinationsupporting
confidence: 91%
“…[17], with a 2% value, and twice the one reported by spin-orbit torque in Ref. [7]. The method that we present here enables us to make a comparison by getting rid of many artefacts that seem to be the cause of a broadening of the results obtained in the literature.…”
Section: Spin Diffusion Length and Spin Hall Angle Determinationmentioning
confidence: 56%
See 2 more Smart Citations
“…Cu-Ir [20][21][22][23][24] , Cu-Bi 25 , Cu-Pt [26][27][28] , Au-Pt 29,30 , and Au-W 31 . Cu-Ir system is an interesting SH material because neither Cu nor Ir exhibits remarkable SHE 32 . Niimi and co-workers 20 investigated the SHE of Ir-doped Cu with the Ir concentration range between 1% and 12%, which exhibited the large α SH of~2.1%.…”
mentioning
confidence: 99%